Concurrent immune checkpoint blockade for enhanced cancer immunotherapy utilizing engineered hybrid nanovesicles - Liu, Yuxuan; Yang, Fuxu; Li, Zhimin; Wang, Ting; Mu, Yeteng; Fan, Yuxin; Xue, Han; Hu, Xiuli; Guan, Xingang; Feng, Hongxia (Frontiers in Pharmacology, 2024)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, demonstrating unprecedented efficacy against advanced cancers. However, their clinical applications are significantly hampered by low overall response rates. Dual blockade of two immune checkpoints represents a promising strategy to enhance immunotherapeutic efficacy. In this study, we developed hybrid cell membrane nanovesicles adorned with PD-1 and SIRPα receptors for combination immunotherapy in melanoma. Our hybrid nanovesicles (PD-1/SIRPα NVs) demonstrated high specificity to PD-L1 and CD47 ligands, facilitating the phagocytosis of melanoma cells by macrophages. In a melanoma mouse model, PD-1/SIRPα NVs significantly suppressed 77% of tumor growth and elicited a robust antitumor immune response for immunotherapy. In conclusion, our findings highlight the promising potential of PD-1/SIRPα NVs as novel and effective ICIs for cancer immunotherapy.